Comprehensive two-dimensional soot diagnostics based on laser-induced incandescence (LII) - Will, Stefan; Leipertz, Alfred; Schraml, Stephan (1996)
A strategy for a comprehensive description of soot sizes and concentrations is described, which relies on various two-dimensional techniques based on laser-induced incandescence (LII) and elastic scattering. Time-resolved LII (TIRE-LII) is an important tool in this process, it allows a direct measurement of primary particle size d(p) as a central quantity for the description of soot. The paper discusses the essential features of the method which is based on the acquisition of the LII signals at two delay times after an initial laser pulse, where monomer size can be deduced from the local signal ratio. Delays of about 100 and 800 ns should be chosen as moments of observation in order to obtain precise information for a aide range of primary particle sizes. Local soot volume fractions f(v) may be directly obtained from the prompt LII signal, where a necessary calibration factor can be deduced from a simple line-of-sight extinction measurement. In combination with elastic scattering, this technique can also be used to give relative values for the volume-equivalent diameter D of soot clusters. Additionally, the local mean number n of monomers within a cluster and number concentrations N-p and N-a of primary particles and aggregates, respectively, can be determined, although some uncertainties persist regarding the absolute monomer sizes measured, and some data can be given only on a relative basis, experimental results obtained for the upper region of a laminar ethene diffusion flame are in good agreement with the established models of soot oxidation and aggregation.